(untitled) (Asian Journal of Plant Biology, 2014)
The third generation biofuels such as algal biodiesel is the future potential source of renewable energy. Recently Dewan et al. (2012) developed a drop-based microfluidics device platform to investigate cellular growth kinetics of single and few cells of Chlorella vulgaris. The results showed the typical asymmetric sigmoidal growth pattern. Since there exists a variety of models for describing the growth profile of microorganism such as logistic, Gompertz, Richards, Schnute, Baranyi-Roberts, Von Bertalanffy, Buchanan three-phase and more recently Huang models, the growth curves exhibit under such conditions would be an excellent study for finding the best model. The Buchanan three-phase model was chose as the best model based on statistical tests such as root-mean-square error (RMSE), adjusted coefficient of determination (R2), bias factor (BF), accuracy factor (AF), corrected AICc (Akaike Information Criterion) and F-test. Parameters obtained from the growth fitting exercise were maximum specific growth rate (mmax), lag time (l) and maximal number of cells achieved per droplet (Ymax) with the values of 1.301 (day-1), 1.861 (day) and 77 (no of cells/droplet), respectively. The parameters obtained from fitting the algae growth curve using this model can bed used for further modeling and optimization exercises for identifying key controlling parameters of the microfluidic devices.